2019
DOI: 10.1111/iji.12414
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of SUMO1 and POU2AF1 in whole blood from rheumatoid arthritis patients and at risk relatives

Abstract: Rheumatoid arthritis (RA) is a systemic autoimmune disorder characterized by chronic and symmetrical inflammation of synovial tissue with subsequent joint destruction. SUMO1 is an important regulator of apoptosis through non‐canonical mechanism in synovial fibroblasts, and POU2AF1 is a known B‐cell transcriptional co‐activator. The specific objective of this study was to measure the expression of SUMO1 and POU2AF1 on first‐degree relatives of patients with RA and also in the preclinical and clinical stages of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…POU2AF1 was identified when comparing arthritis versus healthy or ACPA + individuals, suggesting that the downregulation of such genes starts after the onset of symptoms in RA patients. Also, a significant correlation was identified for POU2AF1 and disease progression with a downward trend for those with established RA 19 .…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…POU2AF1 was identified when comparing arthritis versus healthy or ACPA + individuals, suggesting that the downregulation of such genes starts after the onset of symptoms in RA patients. Also, a significant correlation was identified for POU2AF1 and disease progression with a downward trend for those with established RA 19 .…”
Section: Discussionmentioning
confidence: 89%
“…Computational inference of TF activities based on putative target genes using expression data is constantly gaining ground as a way to obtain mechanistic and functional insights from the transcriptome. This abstraction of the transcriptome through TFs activity reduces the number of features, and allows for the identification of master regulators responsible for different cellular phenotypes [14][15][16][17][18][19][20][21][22][23][24][25] . In our approach, we use publicly available transcriptomic data of synovial tissue and the tool CoRegNet 24 to infer a reference co-regulatory network.…”
mentioning
confidence: 99%
“…59 POU2AF1 is another gene that has not been characterized within the GC literature but has been found to be a high-risk gene in gastrointestinal stromal tumors, a type of soft tissue sarcoma and rheumatoid arthritis. 60,61 Again, the mixed subtype is molecularly different from the intestinal and diffuse gastric subtypes based on this genetic pathway analysis with notably less involvement of metabolism related genes. Although this is expected due to its difference in subtyping, the mixed gastric subtype has a much smaller representation within the literature than the intestinal and diffuse types and it is clear that further investigation is needed.…”
Section: Genetic Analysis Of Downregulated Gc Genes Using Lauren Typementioning
confidence: 88%
“…Another research reported that increasing expression of NPY1 may promote cartilage matrix degradation and chondrocyte hypertrophy, affecting the progression of OA [ 41 ]. POU2AF1 known as a B cell transcriptional coactivator was found to have a significant correlation with disease progression by assessing gene expression in whole blood from RA patients [ 42 ]. Notably, these previous studies increase the credibility of the hub genes that were identified in our study.…”
Section: Discussionmentioning
confidence: 99%